Selected respondent characteristics and training program characteristics as determinants of trainees' perceptions of self-efficacy - Chan, Angelina Wan Sian; Rusli, Ahmad; Azman, Ismail; Wan Khairuzzaman, Wan Ismail (Universiti Teknologi Malaysia, 2011)
This study was conducted to examine the effect of selected respondent characteristics and training program characteristics on trainees’ perceptions of self-efficacy using a sample of 74 usable questionnaires gathered from employees in an electrical company in Sarawak, Malaysia. The outcomes of one-way analysis of variance (ANOVA) showed that none of the demographic characteristics of the respondents had a significant impact on their perceived levels of self efficacy. Conversely, the results of multiple regression analysis confirmed that trainees’ self regulations did act as an important determinant of trainees’ perceptions of self-efficacy. As such, the authors recommend that a positive self-talk session daily before starting work should be implemented to boost employees’ self regulation in the organizational sample.